Application of Indocyanine Green Enhanced Fluorescence in Esophageal Surgery: A Mini Review - Tamburini, Nicola; Chiozza, Matteo; Maniscalco, Pio; Resta, Giuseppe; Marino, Serafino; Quarantotto, Francesco; Anania, Gabriele; Cavallesco, Giorgio (Frontiers in Surgery, 2022)
Despite recent technological innovations and the development of minimally invasive surgery, esophagectomy remains an operation burdened with severe postoperative complications. Fluorescence imaging, particularly using indocyanine green (ICG), offers the ability to address a number of issues faced during esophagectomy. The three main indications for the intraoperative use of ICG during esophagectomy are visualization of conduit vascular supply, allow identification of sentinel nodes and visualization of the thoracic duct. The purpose of this mini review is to present an overview of current practice in fluorescence imaging utilizing ICG during esophagectomy, as well as to demonstrate how this technology can guide lymphadenectomy and reduce surgical morbidity such as anastomotic leaking and chylothorax.